Automobile Rental System - Azmi, Nur Aliah Nafisah; Norlida Hassan, (Applied Information Technology And Computer Science, 2024)
The web-based rental automobile system can enhance the performance of the current manual system. An automobile rental service enables customers to reserve vehicles for a predetermined amount of time and pay for their use. Users can typically browse the available automobiles on the system's website or mobile application, choose their preferred rental duration, and book a vehicle there. A physical site where the rental automobiles can be picked up and returned may also be part of the system. A vehicle is only rented out when it is available, thanks to the car rental system that keeps track of each vehicle's availability. This system was developed by using Visual Studio Code software and php MyAdmin as a database. The development is using a structured approach and prototyping methodology as a guideline. The goal of this project is to make it easier for automobile agencies to manage their assets and for customers to make vehicle reservations